Acehnese idioms among Acehnese adolescents: What is Pèh Tèm? - Ida Muliawati; Faizatul Husna; Nyak Mutia Ismail; Fera Busfina Zalha (Proceedings of AICS - Social Sciences, 2017)
Regarding the phenomenon of language contacts that happen nowadays, a lot of traditional languages are in the threat of extinction, including Acehnese language (Aziz Amery, 2016). Many Acehnese adolescents, recently, have discriminated the language and, too, they have preferred to use Bahasa Indonesia in their daily life contexts compared to the Acehnese language. This concerned issue, as a result, would bring an effect on the existence of Acehnese language in the future as well as its varieties such as idioms. These idioms constitute spoken or figurative language have been existing side by side among Acehnese people and cultures from long time ago. Those idioms are magnified not only to express emotional feeling but also to soften utterances. Consequently, this study aimed at investigating Acehnese adolescents’ understanding about Acehnese idioms since idiomatic expressions depict language users’ proficiency. Qualitative research designed was used and the data were collected through a questionnaire set consisting of 10 Acehnese idiomatic expressions. There were 51 respondents, aged within 18-21 years old who all are indigenous Acehnese. The result suggests that Acehnese adolescents are still knowledgeable about Acehnese idioms. There are 72.8% of the whole respondents who are considered to understand the idioms asked in the questionnaire sets. From additional data, it was obtained that those who did not understand the expressions come from different language continuum. In conclusion, Acehnese adolescents are still aware of the idiom use in Acehnese language. And most importantly, they still understand those expressions.